Soil heatflux under coconut (Cocos nucifera Linn) in an humid tropical oxisol - SAMBASIVARAO, A; VARADAN , KM; VAMADEVAN, VK (MAUSAM, 1986)
The heatflux into an oxisol under coconut in an humid tropical climate was analysed. The peak daily solar radiation and air temperature during dry period (December-May) in this region goes upto 1050 Wm-1 and 35° C respectively. The maximum surface soil (2,5 cm depth) temperature observed in an open field was 62° C on a summer day. The diurnal variation of soil temperature in the open field was between 33° and 45°C at 5 cm depth and it was reduced by 2-7° C due to coconut canopy and by 1-7° C due to natural mulch material. The heat capacity and diffusivity values of the soil were 0.4315 cal cm-2 oC-l and 0.596 x l0-3sec-1 respectively at PWP (permanent wilting point) moisture content. The diurnal heat flux into 5-10 cm layer of soil was between +0,412 and -0,165 cal cm-1 h~ in the open field, whereas it ranges between +0,494 and -0.296 cal cm-1hr-l in the coconut garden. The maximum surface heat flux into 2.5-5.0cm depth was 6.42 cal cm-1 hr-l. Mulching around the basin of the coconut tree causes heat flow to be either at equilibrium or negative. The maximum heatflow into 5-10 cm layer (1430 IST) was up to 0.849 cal cm-. hr-1 in different seasons and it is not related to soil moisture content.